Word Recognition Memory in Adults with Attention-Deficit/Hyperactivity Disorder as Reflected by Event-Related Potentials - Prox-Vagedes, Vanessa; Steinert, Stefanie; Zhang, Yuanyuan; Roy, Mandy; Dillo, Wolfgang; Emrich, Hinderk M.; Dietrich, Detlef E.; Ohlmeier, Martin D. (Frontiers in Human Neuroscience, 2011)
Objective: Attention-deficit/hyperactivity disorder (ADHD) is increasingly diagnosed in adults. In this study we address the question whether there are impairments in recognition memory. Methods: In the present study 13 adults diagnosed with ADHD according to DSM-IV and 13 healthy controls were examined with respect to event-related potentials (ERPs) in a visual continuous word recognition paradigm to gain information about recognition memory effects in these patients. Results: The amplitude of one attention-related ERP-component, the N1, was significantly increased for the ADHD adults compared with the healthy controls in the occipital electrodes. The ERPs for the second presentation were significantly more positive than the ERPs for the first presentation. This effect did not significantly differ between groups. Conclusion: Neuronal activity related to an early attentional mechanism appears to be enhanced in ADHD patients. Concerning the early or the late part of the old/new effect ADHD patients show no difference which suggests that there are no differences with respect to recollection and familiarity based recognition processes.